Unraveling microbial shifts and plant growth responses in Chrysanthemum ‘Merlino’ due to artificial root exudates in horticultural substrates - Pot, Steffi; De Tender, Caroline; Ceusters, Johan; Debode, Jane; Vancampenhout, Karen (Frontiers in Horticulture, 2025)
IntroductionPlant growth and health are significantly influenced by the composition, activity, and diversity of the rhizosphere microbiome. Developing strategies to modify the rhizosphere microbiome to foster beneficial interactions with plants therefore is a promising avenue for sustainable plant production. One such strategy involves the addition of artificial root exudate compounds. This study evaluates the effects of artificial root exudates on the growth and performance of Chrysanthemum ‘Merlino’ and its rhizosphere microbiome.MethodsHorticultural substrates, both peatand compost-based, were supplemented with two concentrations of artificial root exudates containing fructose, glucose, sucrose, succinic acid, malic acid, arginine, serine, and cysteine. Twelve different treatments were tested in total. Plant physiological parameters, including root development, plant growth, and photosynthetic performance, were monitored to assess plant growth and stress responses. Microbial diversity shifts were analyzed using amplicon metabarcoding of the 16S rRNA gene (bacteria) and ITS region (fungi), alongside assessments of enzyme activity (alkaline phosphatase and urease) and microbial metabolic diversity.ResultsOur findings revealed significant impacts on microbial communities in the rhizosphere. Addition of artificial root exudates caused shifts in the bacterial and fungal community composition in both peatand compost-based substrates. The relative abundance of certain fungi increased in treatments with artificial root exudates, particularly those capable of metabolizing hexose or pentose sugars. That lead to a decrease in overall fungal diversity. Although bacterial diversity was not affected, the addition of artificial root exudates enhanced their metabolic diversity. Moreover, the application of artificial root exudates increased the activities of alkaline phosphatase and urease enzymes. Anticipated positive effects on plant growth were not observed: high concentrations of artificial root exudates (three weekly applications of 250 mg C g−1 substrate) resulted in reduced root development across all four horticultural substrates. Additionally, the highest concentration of artificial root exudates appeared to induce plant stress in peat-based substrates, as evidenced by lower dry mass of the plants and reduced Fv/Fm and PIabs.DiscussionWhile artificial root exudates significantly alter the rhizosphere microbiome, they do not necessarily promote plant growth and may, depending on the composition and concentration, induce stress and inhibit root development in horticultural substrates.